Rhizosphere chemistry of young rubber tree (Hevea brasiliensis) in acidic soils of Kerala, India - Ambily, K.K. (Global Soils Conference 2024. Caring Soils beyond Food Security: Climate Change Mitigation & Ecosystem Services, 19-22 November 2024, Indian Society of Soil Science, New Delhi, p. 391. Abstracts., 2024)
The rhizosphere, characterized by the small area adjacent to plant roots is the important zone of nutrient changes and nutrient activity of plants which governs the nutrient release and uptake for plant growth. Rhizosphere chemistry is species-specific near roots. Rubber (Hevea brasiliensis), an important source of natural rubber generally growing in acidic conditions is a major crop for economic returns. The initial growth (3-4 years) and establishment of rubber plants are most critical, a knowledge of rhizosphere chemistry is important for adopting soil management methods to improve the growth of rubber plants and hence the present study was conducted. It comprised the rhizosphere soil sample collection (0-15 cm depth) from the rubber plantation (2-3 years age) to know the chemical elemental concentrations in the rhizosphere soil (soil adhered to fresh fine roots) in different agro-climatic zones of Kerala. Results indicated that rhizosphere soil has high available P, exchangeable AI which pointed out the need for a specific management option in young rubber trees.
Keywords: Rhizosphere; Acidic soil